PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI KANTOR CAMAT LUBUKLINGGAU SELATAN II KOTA LUBUKLINGGAU - Ervina Cahyani; Mulyadi Mulyadi (Jurnal Interprof, 2017)
The purpose of this research is (a) to determine the effect of leadership and motivation of the employee's performance at the district office South Lubuklinggau II, (b) To determine how much influence the motivation of the employee's performance at the district office South Lubuklinggau II. (c) to determine how much influence the leadership and motivation simultaneously on the performance of employees at the district office South Lubuklinggau II T-test leadership variable (X1) on the motivation to showed the value t = 3.155 greater than the value ttable 2,021 with a significant level = 0.000 <(α) 12:05, df (n-2) 35-3 = 31 is equal to 1.695, this shows Ho rejected and Ha accepted and in partial leadership style has a significant influence on employees motivation at the district office South Lubuklinggau II T test results above can be explained that the motivation variable (X2) to employee performance showed the value t = 2.572 greater than the valuettable 2,021 with a significant level = 0.000 <(α) 12:05, df (n-2) 35-3 = 31 is amounted to 1.695, suggesting that Ho rejected and Ha accepted and in partial work discipline has a significant influence on employees performance at the district office South Lubuklinggau II Testing of the hypothesis that F account obtained was 4.083> F table = 3.26 significance level simultaneously and significance is 0.000 <(α) = 0.05 df = n - k = 35 - 3-1 = 31 amounted to 1,695 so that Ho rejected and Ha accepted. Means shows that together (simultaneously) the independent variable X1 (leadership) and X2 (motivation) have a significant effect on the dependent variable Y (employees performance) so the hypothesis proved to be true and acceptable